Heuristics : the foundations of adaptive behavior - Gigerenzer, Gerd.; Hertwig, Ralph; Pachur, Thorsten (New York ; Oxford : Oxford University Press, 2011)
How do people make decisions when time is limited, information unreliable, and the future uncertain? This book tells how based on the work of Herbert Simon, the Adaptive Behavior and Cognition (ABC) Group has developed a research programme on simple heuristics, also known as fast and frugal heuristics.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Keywords: Adaptability (Psychology)